Cultural pluralism as adult education: Alain Locke, Horace Kallen, and the discourse of difference - Talmade Guy; Linda O’Neill; Amy D. Rose (Adult Education Research Conference, 1996)
This paper examines the development of the theories of cultural pluralism as laid out by Horace Kallen and Alain Locke. It places their ideas within their own historical context and attempts to link these writers to the current debates about multicultural education today.